Análise numérica da compartimentação vertical em edifícios de múltiplos andares em situação de incêndio - Corrêa Junior, Jaete (2023)
Fires cause significant disruptions and damages, and vertical compartmentalization is a control measure implemented through projections. In Brazil, there are no standards from the Brazilian Association of Technical Standards on the subject. Each state is responsible for formulating its own technical instructions, Which are based on consensus and occasionally lack scientific grounding. Hence, experimental and numerical research plays a crucial role in advancing scientific understanding. This study aims to analyze numerically, using the Fire Dynamics Simulator (FDS) software, the effectiveness of employing both horizontal projections and the sum of spandrel and horizontal projections of structures outlined in the Technical Instruction of the Fire Department of the State of São Paulo to combat the spread of external vertical fires on the facade. Temperature and heat flux measurements on the facade were compared with the autoignition values of materials on upper floors of the building. The main results indicate that spandrels in the facade of the same compartment on fire influence the elevation of the temperature on the upper floor, as well as the opening rates in the facades; lower opening rates result in higher temperatures. Models with only horizontal projections showed greater efficacy compared to those with a sum of spandrel and horizontal projections, and the presence of the spandrel component causes the fire to project near the building, increasing the temperature on the upper floor. Despite models with a sum of spandrel and horizontal projections not having the same efficacy for a fire with a load of 300 MJ/m², there would be no propagation of external vertical fires due to temperatures on the facade of the upper floor being incapable of causing autoignition of materials commonly found on building facades.